2002
DOI: 10.1039/b201002j
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to a photocleavable protecting group for alcohols

Abstract: A new protecting group for the alcohol functionality was devised and shown to be removed photochemically under ultraviolet light in the presence of a radical scavenger in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…BHQ-caged carboxylates ( 181b ), phosphates ( 181c ), and diols ( 182 ) are efficiently released under simulated physiological conditions using single-photon and two-photon activation. 331 In addition, a (2-phenylquinolin-4-yl)methyl group 333 and the corresponding arylmethylsulfonyl analogue 334 have been proposed as PPGs for alcohols and amines, respectively.…”
Section: Arylmethyl Groupsmentioning
confidence: 99%
“…BHQ-caged carboxylates ( 181b ), phosphates ( 181c ), and diols ( 182 ) are efficiently released under simulated physiological conditions using single-photon and two-photon activation. 331 In addition, a (2-phenylquinolin-4-yl)methyl group 333 and the corresponding arylmethylsulfonyl analogue 334 have been proposed as PPGs for alcohols and amines, respectively.…”
Section: Arylmethyl Groupsmentioning
confidence: 99%
“…4 To date the major effort has been devoted to mask phosphates, carboxylates, and alcohols as biologically the most significant functional groups. 5 The hydroxy groupcontaining molecules can be effectively protected by a variety of PPGs, for example, as 2-nitrobenzyl, 6 3,5-dimethoxybenzoin, 7 phenacyl 8 and anthraquinon-2-yl methyl 9 carbonates, or 9phenylxanthyl, 10 2-benzoylbenzoic, 11-13 quinolyl methyl, 14 or hydroxystyrylsilyl 15 derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Photoremovable protecting groups are of interest since they have demonstrated applications in photolithography, synthetic organic chemistry, and biochemistry. Recently, Porter et al reported that photolysis of 2-benzoylbenzoate esters 1 in 2-propanol yielded the corresponding alcohol and lactone 3 1 whereas irradiation of 1 in the presence of the electron donor cyclohexylamine also released the alcohol but led to the formation of lactone 2 . Presumably these reactions take place by photoreduction of 1 to form 2-(α-hydroxyphenylmethyl)benzoic ester, which then undergoes intramolecular lactonization to release the alcohol.…”
Section: Introductionmentioning
confidence: 99%